Assessing the factors affecting the perception of farmer-beneficiaries on the implementation of CARP support services a case in Macarimbang ARC, Maguindanao, Philippines - Linso, Farhana Jane S. (School of Management, University of the Philippines Mindanao, 2016)
This study evaluates the implementation of CARP support services based on the perception of the farmer-beneficiaries in Macarimbang ARC. Tobit model is used to analyze the relationship between the socio-demographic and economic characteristics of the farmer-benefeciaries and their perception on the implementation of the programs under each project component of CARP ? SILCAB, SARED, and AFAES. Results have shown that the socio-demographic and economic factors significantly affect the satisfaction of the respondents towards CARP support services. Farmers with larger household size, farm size, and farm income tend to be more satisfied of the said programs. On the other hand, the members of the organizations have lower satisfaction towards the said programs. Moreover, the farmer-beneficiaries believe that the implementation of SILCAB and AFAES programs are successful, while SARED is not successful. In general, farmer-beneficiaries are satisfied of the CARP support services.